Nitrate-rich vegetables do not lower blood pressure in individuals with mildly elevated blood pressure: A 4-wk randomized controlled crossover trial - Blekkenhorst, L.; Lewis, J.; Prince, R.; Devine, A.; Bondonno, N.; Bondonno, C.; Wood, L.; Puddey, I.; Ward, Natalie; Croft, K.; Woodman, R.; Beilin, L.; et al. (American Society for Nutrition, 2018)
Background: Emerging evidence suggests that increasing intakes of nitrate-rich vegetables may be an effective approach to reduce blood pressure. Objective: Our primary aim was to determine whether daily consumption of nitrate-rich vegetables over 4 wk would result in lower blood pressure. Design: Thirty participants with prehypertension or untreated grade 1 hypertension were recruited to a randomized controlled crossover trial with 4-wk treatment periods separated by 4-wk washout periods. Participants completed 3 treatments in random order: 1) increased intake (∼200 g/d) of nitrate-rich vegetables [high-nitrate (HN); ∼150 mg nitrate/d], 2) increased intake (∼200 g/d) of nitrate-poor vegetables [low-nitrate (LN); ∼22 mg nitrate/d], and 3) no increase in vegetables (control; ∼6 mg nitrate/d). Compliance was assessed with the use of food diaries and by measuring plasma nitrate and carotenoids. Nitrate metabolism was assessed with the use of plasma, salivary, and urinary nitrate and nitrite concentrations. The primary outcome was blood pressure assessed by using 24-h ambulatory, home, and clinic measurements. Secondary outcomes included measures of arterial stiffness. Results: Plasma nitrate and nitrite concentrations increased with the HN treatment in comparison to the LN and control treatments (P < 0.001). Plasma carotenoids increased with the HN and LN treatments compared with the control (P < 0.01). HN treatment did not reduce systolic blood pressure [24-h ambulatory—HN: 127.4 ± 1.1 mm Hg; LN: 128.6 ± 1.1 mm Hg; control: 126.2 ± 1.1 mm Hg (P = 0.20); home—HN: 127.4 ± 0.7 mm Hg; LN: 128.7 ± 0.7 mm Hg; control: 128.3 ± 0.7 mm Hg (P = 0.36); clinic—HN: 128.4 ± 1.3 mm Hg; LN: 130.3 ± 1.3 mm Hg; control: 129.8 ± 1.3 mm Hg (P = 0.49)] or diastolic blood pressure compared with LN and control treatments (P > 0.05) after adjustment for pretreatment values, treatment period, and treatment order. Similarly, no differences were observed between treatments for arterial stiffness measures (P > 0.05). Conclusion: Increased intake of nitrate-rich vegetables did not lower blood pressure in prehypertensive or untreated grade 1 hypertensive individuals when compared with increased intake of nitrate-poor vegetables and no increase in vegetables. This trial was registered at www.anzctr.org.au as ACTRN12615000194561.